(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
In enrich students’ vocabularies is a major point on this studies while college students are fulfillment in improve their vocabularies, they think they are greater clever. Easy for them to recognize by using what they pay attention and examine. They may be smooth to specific what they feel because they already have a masses of vocabulary. They sense extra confidents with what they have already got. Every other pursuits in this research are to peer how powerful using English children short story to enhance students’ Vocabulary by means of doing treatment in elegance, translate the paragraph of the short tale and doing an assesment in line with vocabulary rubric The time that research used to do that reserach is four weeks start from february till march by means of using quantitative studies. The information are accrued through using pre-experimental layout with one organization pre-check and publish-test. The researcher implemented the purposive sampling technique to take the sample. The sample in this research became magnificence 7B with populace 26 students at SMP IT Darurrahman, 2021/2022 academic year. The instrument of this research turned into vocabulary check. The research effects that the suggest score of put up-take a look at become 74.03 which better than the imply rating of pre-take a look at turned into only 33.84. It may be concluded that scholar vocabulary had improve after being given treatment by way of the usage of English Children Short Story.That is supported by using the t-test score is (32.5>84). It approach that Null hypothesis (H0) is rejected even as the alternative hypothesis (H1) is well-known. This findings indicated that the usage of English Children Short story improve the scholars’ vocabulary mastery.